Nursing experience of a patient with Stanford type A aortic dissection complicated with recurrent gastrointestinal bleeding (1例Stanford A型主动脉夹层合并反复消化道出血患者的护理体会) - CHANG Yuesi (常粤思) (Association of Integrative Nursing, 2022)
This paper summarized the nursing experience of a patient with Stanford type A aortic dissection complicated with recurrent gastrointestinal bleeding. Key issues of nursing included hemodynamic monitoring, airway management, early identification of gastrointestinal bleeding, postoperative nursing of endoscopic hemostasis for hemorrhage, nursing of jejunostomy, fluid management, early rehabilitation, and psychological care. (本文总结1例Stanford A型主动脉夹层合并反复消化道出血患者的护理经验, 包括血流动力学监测、呼吸道管理、消化道出血的早期识别、消化道内镜下止血术后护理、空肠造瘘护理、出入量的管理、早期康复以及心理护理。)